2009
DOI: 10.1111/j.1365-2761.2009.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the introduced cyprinid herpesvirus 3 in a wild population of common carp, Cyprinus carpio L.

Abstract: Cyprinid herpesvirus 3 (CyHV-3), which causes a lethal disease in common carp, Cyprinus carpio L., and koi, C. carpio koi, first occurred in Lake Biwa, Japan in 2004. To elucidate distribution of CyHV-3 in a wild common carp population, we conducted a PCR survey of CyHV-3 among such fish in Lake Biwa in 2006. Only 6% (1/18) of the common carp smaller than 300 mm were positive with PCR, whereas 31% (18/58) of fish larger than 300 mm were positive. To evaluate their past exposure to CyHV-3 infection based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 20 publications
4
58
0
Order By: Relevance
“…This pattern was previously described for the common carp population in Lake Biwa in 2006 (Uchii et al, 2009). In this study, we found an identical trend in 2008 and 2009 (Figure 2), suggesting that newly matured hosts were subject to CyHV-3 infection in every year sampled.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This pattern was previously described for the common carp population in Lake Biwa in 2006 (Uchii et al, 2009). In this study, we found an identical trend in 2008 and 2009 (Figure 2), suggesting that newly matured hosts were subject to CyHV-3 infection in every year sampled.…”
Section: Discussionsupporting
confidence: 72%
“…Serum anti-CyHV-3 antibodies were quantified using the enzyme-linked immunosorbent assay (ELISA) according to Uchii et al (2009), with some modifications. Pooled sera of 10 wild common carp diagnosed CyHV-3 positive by PCR were used as a positive control and pooled sera of 10 cultured common carp never exposed to CyHV-3 were used as a negative control.…”
Section: Measurement Of Serum Anti-cyhv-3 Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…KHV can become latent inside the leukocytes of healthy koi with probable exposure to the virus. In wild populations, KHV can remain as carrier in asymptomatic fish and act as reservoir of infection [83]. Several months after initial exposure to the virus, temperature-dependent reactivation of KHV infection can occur in exposed fish [19,78].…”
Section: Latency In the Hostmentioning
confidence: 99%
“…These antibodies are detected in the serum at 3 weeks after experimental infection and in survivors after 1 year following a natural infection [1,39,78,81]. KHV infection induces a high prevalence (54 %) of KHV specific antibodies in surviving wild fish population [83]; while studies in farmed fish of England show almost 85-93 % of fish are seropositive by ELISA, even 1 year after disease outbreak [81]. This indicates that ELISA is a valuable method of establishing previous exposure of KHV in apparently healthy fish.…”
Section: Detection Of Khv Antigen/antibodiesmentioning
confidence: 99%